A BASIC LAND SALE AGREEMENT SOFTWARE: EXPLOITING ICT IN LEGAL PRACTICE IN NIGERIA - Fapetu, Oluwaseun Samson; Taiwo, Elijah Adewale (International Journal of Research -GRANTHAALAYAH, 2021)
The use of Information Communication Technology (ICT) has permeated every profession, sector and facet of life. Although it has been slow in its application to legal practice in Nigeria, the prospect of ICT in law is promising and unending and it has resulted in the field of Artificial Intelligence (AI) and Law. AI and Law has many branches of which legal document automation forms an important part with high applications to drafting agreements. The paper examines the functionality of a programme written by the first author that automatically generates land sale agreements between natural persons, with the aim of ascertaining if the programme conforms with the appropriate provision of applicable laws. The paper examines the laws applicable to land sale agreements in Nigeria and finds that the document produced by the programme conforms with the provisions of these Laws. The paper also examines the issues that may arise in the use of the programme or similar programmes.